PERANAN TOUR PLANNER SEBAGAI JASA KONSULTAN PERJALANAN WISATA DI PT SARANA PESONA BIMA WISATA YOGYAKARTA - , EKO PRASETYO AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this recent years the Tourism Industry plays an important role in improving the country's foreign exchange earnings outside of the non oil and gas sector. In the midst of the global economic crisis which occurred in Indonesia, Indonesia's tourism industry continues to grow, even it shows the numbers that continue to rising. The increased growth of the tourism industry in Indonesia can not be separated from the role of a travel agent or a travel agency that has been continue selling the tour packages either itâs an inbound tour package or an outbound tour package. Based on that, the writer wanted to know the role of a tour planner in preparing and selling the tour packages. Another purpose of this paper is to find out how the scope, the performance mechanism, and also the tour planner role of being a travel consultant for prospective tourists who would become their partners. Tour Planner is one of a very important part in a travel agency. As the tour and travel consultant, a tour planner gives a suitable option for tourists who will be conducting tours. Tour Planner will give informations about the best destinations in the tourist destination, making an interesting tour packages, up to do the maximum service for the tourists. Therefore the role of a tour planner is very vital in a travel agency.